PENGEMBANGAN MOBILE APPLICATION TRACER STUDY (STUDI KASUS : IBI DARMAJAYA) - M. Miftakul Amin (IIB Darmajaya, 2011)
IBI Darmajaya has several times held a tracer study. However, because the tracer study was done independently in each department, then it’s aspects vary greatly according to the interests of each department. Tracer studies also can not be used as a representing IBI Darmajaya’s graduates overall. This study presents an instrument by applying a tracer study in charging mobile application. Mobile application is built using the Wireless Application Protocol (WAP) as a content applications. The results of this study was obtained by a mobile software application that makes it easy for IBI Darmajaya’s graduates to fill out questionnaires of tracer study without experiencing barriers of distance and time.Keywords: Mobile Application, Tracer Study